High-Efficiency Flexible Organic Photovoltaics and Thermoelectricities Based on Thionyl Chloride Treated PEDOT:PSS Electrodes - Wan, Juanyong; Fan, Xi; Li, Yunfei; Li, Pengcheng; Zhang, Ting; Hui, Kwun Nam; Huang, Huihui; Kang, Kai; Qian, Lei (Frontiers in Chemistry, 2022)
Conducting polymers have received tremendous attentions owing to their great potentials to harvest both luminous- and thermal energies. Here, we reported a flexible transparent electrode of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) with highly electrical conductivity and raised Seebeck coefficient via thionyl chloride treatments. The comprehensive studies of optical-, electrical-, morphological-, structural- and thermoelectrical properties, work function, and stability of the PEDOT:PSS transparent electrodes were systematically evaluated and described. On the basis of the PEDOT:PSS transparent electrodes, the resultant flexible organic solar cells yielded a high power conversion efficiency of 15.12%; meanwhile, the flexible thermoelectricities exhibited the raised power factor of 115.9 μW m−1 K−2, which outperformed four kinds of rigid thermoelectricities with conventional acid and base treatments.